Ealham, Chris (2010): Anarchism and the city: Revolution and counter-revolution in Barcelona, 1898-1937 - Gorostiza, Santiago (Documents d'Anàlisi Geogràfica, 2012)
Ealham, Chris Anarchism and the city: Revolution and counter-revolution in Barcelona, 1898-1937 Oakland, CA: AK Press, 2010, 263 p. ISBN-13: 978-1-84935-012-9